Thymoquinone' nin uterus tümörlerinde invitro ve invivo etkileri - Timurkan, Hüseyin; Yekeler, Hayreddin; Risvanli, Ali; Gürateş, Bilgin; Bulut, Tevfık Hakan; Aydin, Suleyman; Bulmuş, Özgür (My University, 2009)
-
20.01.2009
Keywords: Onkoloji